Dendrimeric Systems and Their Applications in Ocular Drug Delivery - Burçin Yavuz; Sibel Bozdağ Pehlivan; Nurşen Ünlü (The Scientific World Journal)
Ophthalmic drug delivery is one of the most attractive and challenging research area for pharmaceutical scientists and ophthalmologists. Absorption of an ophthalmic drug in conventional dosage forms is seriously limited by physiological conditions. The use of nonionic or ionic biodegradable polymers in aqueous solutions and colloidal dosage forms such as liposomes, nanoparticles, nanocapsules, microspheres, microcapsules, microemulsions, and dendrimers has been studied to overcome the problems mentioned above. Dendrimers are a new class of polymeric materials. The unique nanostructured architecture of dendrimers has been studied to examine their role in delivery of therapeutics and imaging agents. Dendrimers can enhance drug’s water solubility, bioavailability, and biocompatibility and can be applied for different routes of drug administration successfully. Permeability enhancer properties of dendrimers were also reported. The use of dendrimers can also reduce toxicity versus activity and following an appropriate application route they allow the delivery of the drug to the targeted site and provide desired pharmacokinetic parameters. Therefore, dendrimeric drug delivery systems are of interest in ocular drug delivery. In this review, the limitations related to eye’s unique structure, the advantages of dendrimers, and the potential applications of dendrimeric systems to ophthalmology including imaging, drug, peptide, and gene delivery will be discussed.